Natural Compounds Play Therapeutic Roles in Various Human Pathologies via Regulating Endoplasmic Reticulum Pathway - Run-Hui Ma; Zhi-Jing Ni; Kiran Thakur; Fan Zhang; Yuan-Yuan Zhang; Jian-Guo Zhang; Zhao-Jun Wei (Elsevier, 2020)
Recent advances in cellular markers (cell signaling pathways) indicate their potency in disease progression and also provide therapeutic benefits to biomedicine. Interestingly, in normal functioning cells, endoplasmic reticulum (ER), a membranous intracellular organelle is well characterized for inextricable links in cellular homeostasis through protein synthesis regulation destined for cell-to-cell communication. However, several genetic and ecological aberration impede their vast interplay and reason the buildup of outspread or misfolded proteins, spontaneously leading to multifaceted and dynamic ER stress reaction to escape instant cell dysfunction to trigger cell death which are the key contributors for the development of epidemiological disorders linked with cancer, neurodegeneration, diabetes, viral infections, and other chronic ailments. Consequently, there is great concern in targeting components of specific ER stress signaling pathways, cooperatively recognized as the unfolded protein response (UPR) and its branches in the regime of combating these ER-stress linked pathologies. The significance of natural products in contemporary medication continues to be of a great importance for the generation of novel lead compounds. UPR and its sensors are the targets of several natural compounds for balancing the ER homeostasis with an intent to treat ER stress-related diseases. Here, we focus on several natural products as therapeutic interventions to target ER stress signaling pathways. We mainly updated the information on the ER and its functions responsible for epidemiologically-relevant diseases, as well as extended it to the crosstalk with complex signal transduction pathways related to the ER stress response. Additionally, we also highlighted integrated insights on natural compounds derived ER response biomarkers which can be targeted for therapeutic purposes to deal with unmet biomedical requirements.